Application of the protection motivation theory for predicting COVID-19 preventive behaviors in Hormozgan, Iran: a cross-sectional study - Ezati Rad, Roghayeh; Mohseni, Shokrollah; Kamalzadeh Takhti, Hesamaddin; Hassani Azad, Mehdi; Shahabi, Nahid; Aghamolaei, Teamur; Norozian, Fatemeh (BMC public health, 2021)
The high prevalence and mortality of coronavirus disease 2019 (COVID-19) have made it the most important health and social challenge around the world. However, this disease can be largely prevented by adherence to hygienic principles and protective behaviors. It seems that identifying the processes involved in protective health behaviors can be effective in planning and implementing suitable interventions to encourage the community toward protective behaviors. Therefore, the present study aimed to predict the preventive behaviors of COVID-19 according to the Protection Motivation Theory (PMT). This cross-sectional study was conducted over 2 months in Hormozgan Province, Iran. The study population consisted of all citizens above the age of 15 years. An online questionnaire was used to collect the data. The questionnaire link was available to the participants through social networks. The questionnaire consisted of two sections, including the demographic information and the PMT constructs. All statistical calculations and hypothesis testing were performed in SPSS Version 21 and AMOS Version 21. The significance level was considered to be 0.05 for hypothesis testing. A total of 2032 subjects, with the mean age of 34.84 ± 9.8 years (r = 15-98), participated in this study. Most of the participants were 31-40 years old, female (60.4%), married (72%), urban residents (87.3%), and employed (58.8%). The majority of them also had a bachelor's degree or higher (58.8%). Significant positive correlations were observed between the preventive behaviors of COVID-19 and the perceived vulnerability (r = 0.192, P < 0.001), perceived severity (r = 0.092, P < 0.001), response efficacy (r = 0.398, P < 0.001), self-efficacy (r = 0.497, P < 0.001), and protection motivation (r = 0.595, P < 0.001). On the other hand, significant negative correlations were found between the preventive behaviors of COVID-19 and maladaptive behavior rewards (r = - 0.243, P < 0.001) and perceived costs (r = - 0.121, P < 0.001). The present findings showed that maladaptive behavior reward and fear negatively predicted the protective behaviors. On the other hand, response efficacy and self-efficacy positively predicted the protective behaviors; the impact of self-efficacy was the strongest. Overall, the information provided in this study can contribute to health policymaking in Iran.